2014
DOI: 10.1016/j.celrep.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

APP Homodimers Transduce an Amyloid-β-Mediated Increase in Release Probability at Excitatory Synapses

Abstract: Accumulation of amyloid-β peptides (Aβ), the proteolytic products of the amyloid precursor protein (APP), induces a variety of synaptic dysfunctions ranging from hyperactivity to depression that are thought to cause cognitive decline in Alzheimer's disease. While depression of synaptic transmission has been extensively studied, the mechanisms underlying synaptic hyperactivity remain unknown. Here, we show that Aβ40 monomers and dimers augment release probability through local fine-tuning of APP-APP interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 47 publications
9
121
0
Order By: Relevance
“…Recently, it has been shown that soluble APP and the APP-E1 domain could activate the Akt survival pathway following trophic factor depletion and that this activation involves an interaction of APP or APP-E1 domain with APP-FL [152] . In a similar fashion, Aβ interaction with APP induces G-protein-dependent enhancement of synaptic activity that involves the APP-E1 domain [153] . As previously discussed in section 1, APP-FL possesses the structural ability to bind ligand to its own E1 domain.…”
Section: Secreted App and Putative Ligand-induced Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that soluble APP and the APP-E1 domain could activate the Akt survival pathway following trophic factor depletion and that this activation involves an interaction of APP or APP-E1 domain with APP-FL [152] . In a similar fashion, Aβ interaction with APP induces G-protein-dependent enhancement of synaptic activity that involves the APP-E1 domain [153] . As previously discussed in section 1, APP-FL possesses the structural ability to bind ligand to its own E1 domain.…”
Section: Secreted App and Putative Ligand-induced Signalingmentioning
confidence: 99%
“…As previously discussed in section 1, APP-FL possesses the structural ability to bind ligand to its own E1 domain. This association could initiate subsequent G-protein coupled signaling events by engaging motifs within the cytosolic C-terminal tail of APP [152, 153] . This scenario is reminiscent of a complex formation between a ligand and an autoreceptor.…”
Section: Secreted App and Putative Ligand-induced Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Remaining open questions concern the cellular mechanisms by which soluble Ab species induce neuronal hyperactivity and which of their various forms are most toxic. For instance, Ab dimers were shown to reduce the re-uptake of synaptic glutamate [42] and Ab 1 -40 monomers and dimers were found to enhance the presynaptic release of glutamate [43]. A combination of these effects could increase extracellular levels of residual glutamate and, thereby, promote neuronal hyperactivity.…”
Section: Hippocampal Hyperactivity Precedes Amyloid Plaque Formation mentioning
confidence: 99%
“…Elevated electrical activity in the hippocampus has been observed early in AD in stages preceding the formation of senile plaques [107]. Interestingly, a recent paper suggested that APP molecules may function as surface receptors modulating the Aβ signaling [108]; the Authors showed that neurons in hippocampus became hyperactive at the pre-synaptic site through APP homodimer as pre-synaptic receptor, which binds Aβ40 following a rise in its concentration. If very low Aβ level is essential for the normal dayto-day life in agreement to Puzzo et al [66,67], thus, we can hypothesize that when the level of Aβ peptides is even slightly increased, it causes neuronal hyperactivity and neuronal functional impairment in several brain areas as also frequently reported in MCI patients [109].…”
Section: Neuronal Activity In Admentioning
confidence: 99%